Healthy Living Community Movement: KKN Initiative in Maintaining Environmental Cleanliness - Adi Lusi; Amrina Amrina; Syafiq Amir (Yayasan Adra Karima Hubbi, 2024)
Background. Problems related to waste, pollution and low public awareness of the importance of maintaining cleanliness still occur in many areas. This can worsen public health problems, including an increase in diseases transmitted through waste and poor sanitation. The Healthy Living Community Movement (GERMAS) initiated by the Government aims to encourage people to adopt a healthy lifestyle, including environmental cleanliness. Through Real Work Lectures (KKN), students can play an active role in spreading awareness and implementing environmental cleanliness programs to support the realization of GERMAS at the community level.Purpose. The purpose of this community service program initiative is to increase public awareness of the importance of maintaining environmental cleanliness as part of a healthy lifestyle. In addition, this program aims to empower communities to carry out voluntary and sustainable cleaning activities. Through the active participation of local communities, it is hoped that a cleaner and healthier environment can be created, free from the risk of disease due to poor environmental sanitation.Method. The methods used in this community service program initiative include a participatory approach where students carry out environmental remediation activities with the local community.Results. The results achieved through this community service program initiative show increasing public awareness of the importance of maintaining environmental cleanliness. Many residents have begun to actively participate in mutual cooperation efforts to clean the environment and manage waste better.Conclusion. Inisiatif program pengabdian masyarakat gerakan Komunitas Hidup Sehat ini telah berhasil meningkatkan kesadaran masyarakat akan pentingnya kebersihan lingkungan sebagai bagian dari pola hidup sehat.